The role of impulsive behavior in drug abuse - Perry, Jennifer L.; Carroll, Marilyn E. (Psychopharmacologia, 2008)
Background Impulsivity is a multifaceted construct that has recently been recognized as a factor contributing to enhanced vulnerability to drug abuse. Objectives In the present review, we focus on two facets of impulsivity (and tasks that measure them): (1) impulsive choice (delay discounting task) and (2) inhibitory failure (go/no-go, stop signal reaction time, and five-choice serial reaction time tasks). We also describe how performance on each of these tasks is associated with drug-related behavior during phases of drug abuse that capture the essential features of addiction (acquisition, escalation, and reinstatement of drug-seeking after drug access has terminated). Three hypotheses (H) regarding the relationship between impulsivity and drug abuse are discussed: (1) increased levels of impulsivity lead to drug abuse (H1), (2) drugs of abuse increase impulsivity (H2), and (3) impulsivity and drug abuse are associated through a common third factor (H3). Conclusion Impulsivity expressed as impulsive choice or inhibitory failure plays a role in several key transition phases of drug abuse. There is evidence to support all three nonexclusive hypotheses. Increased levels of impulsivity lead to acquisition of drug abuse (H1) and subsequent escalation or dysregulation of drug intake. Drugs of abuse may increase impulsivity (H2), which is an additional contributor to escalation/dysregulation. Abstinence, relapse, and treatment may be influenced by both H1 and H2. In addition, there is a relationship between impulsivity and other drug abuse vulnerability factors, such as sex, hormonal status, reactivity to nondrug rewards, and early environmental experiences that may impact drug intake during all phases of addiction (H3). Relating drug abuse and impulsivity in phases of addiction via these three hypotheses provides a heuristic model from which future experimental questions can be addressed.